2013
DOI: 10.1371/journal.pone.0070980
|View full text |Cite|
|
Sign up to set email alerts
|

Association between Bone Mineral Density and Incidence of Breast Cancer

Abstract: IntroductionPrevious studies have suggested an inverse relationship between bone mineral density (BMD) and breast cancer incidence. The primary objective of this study was to assess whether BMD is associated with risk of subsequent breast cancer occurrence in the female population of southern Israel.MethodsThe electronic medical charts of women who underwent BMD at the Soroka Medical Center (SMC) between February 2003 and March 2011 were screened for subsequent breast cancer diagnoses. Women were divided by te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…The clinical relevance of our finding that osteoblast-lineage cells instigate systemic changes promoting tumor growth and dissemination is supported by several clinical studies, which have linked alterations in bone homeostasis with the risk of breast cancer (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). High bone mineral density (BMD) has long been associated with increased risk of breast carcinogenesis and increased risk of metastasis in breast cancer patients (42,(44)(45)(46)(47)(48)52).…”
Section: Discussionmentioning
confidence: 67%
“…The clinical relevance of our finding that osteoblast-lineage cells instigate systemic changes promoting tumor growth and dissemination is supported by several clinical studies, which have linked alterations in bone homeostasis with the risk of breast cancer (42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52). High bone mineral density (BMD) has long been associated with increased risk of breast carcinogenesis and increased risk of metastasis in breast cancer patients (42,(44)(45)(46)(47)(48)52).…”
Section: Discussionmentioning
confidence: 67%
“…However, regarding fracture risk of women with BC, study results are conflicting. A number of authors indicated that women with a higher BMD are at higher risk for developing breast cancer suggesting that there is a difference in baseline BMD of women with BC and healthy women [2,3,[20][21][22][23]. Zambetti et al revealed BMD as a significant prognostic factor for local or distant breast cancer recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 However, data on the risk of osteoporotic fractures in women with BC are conflicting. Early studies did not find a lower risk for osteoporotic fracture among patients who developed BC.…”
Section: Introductionmentioning
confidence: 99%